2020
DOI: 10.3390/w12102924
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-Temporal Dynamics of Riverine Nitrogen and Phosphorus at Different Catchment Scales in Huixian Karst Wetland, Southwest China

Abstract: Spatio-temporal dynamics of riverine nitrogen (N) and phosphorus (P) in karst regions are closely linked to hydrological conditions, human activities and karst features in upstream catchments. From October 2017 to September 2019, we undertook 22 sampling campaigns in 11 nested catchments ranging from 21.00 to 373.37 km2 in Huixian karst wetland to quantify forms, concentrations, and fluxes of riverine total nitrogen (TN) and total phosphorus (TP), and to identify spatial and temporal variations of nutrients tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…For this reason, one of the scientific research objectives is to understand the origins of nitrate transformations in the karst systems. High application doses of fertiliser have caused nitrate pollution of the karst aquifer for the cultivations of pineapples [47], rice, corn, rapeseed [48], soybeans [49], beans, tubers, cotton, apple, pear, melons [50], olive trees [51] and other vegetables [52]. These studies indicated that sustainable nitrogen fertilisation practices and rational irrigation are the keys to mitigating nitrate pollution in the karst environment.…”
Section: Fertilisersmentioning
confidence: 99%
See 1 more Smart Citation
“…For this reason, one of the scientific research objectives is to understand the origins of nitrate transformations in the karst systems. High application doses of fertiliser have caused nitrate pollution of the karst aquifer for the cultivations of pineapples [47], rice, corn, rapeseed [48], soybeans [49], beans, tubers, cotton, apple, pear, melons [50], olive trees [51] and other vegetables [52]. These studies indicated that sustainable nitrogen fertilisation practices and rational irrigation are the keys to mitigating nitrate pollution in the karst environment.…”
Section: Fertilisersmentioning
confidence: 99%
“…Karst aquifers characterised by gullies, gaps and fracture networks within the karst architecture are mainly subjected to rapid transport of pollutants from surface to groundwater, affecting water quality [48]. Therefore, the water cycle is pollutant transfer's primary driver and carrier [141].…”
Section: Influences Of the Temporal Dynamic Of Karst Systemsmentioning
confidence: 99%
“…The Huixian karst wetland is considered as the largest karst wetland in South China (Cai et al, 2009;Chen et al, 2020;Pan et al, 2020) and has been listed as a national wetland park since 2012. This wetland has crucial ecological functions with respect to the Li River, including flood control, water purification, and biodiversity support (Qin et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…This wetland has crucial ecological functions with respect to the Li River, including flood control, water purification, and biodiversity support (Qin et al, 2020). Because of its significant social-ecological value to nearby regions, many recent studies have reported on the hydrology (Pan et al, 2020), soil properties (Li et al, 2017b), contamination (Chen et al, 2020;Huang et al, 2020), and microalgal and bacterial communities (Yan et al, 2020) of the Huixian karst wetland.…”
Section: Introductionmentioning
confidence: 99%